(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The electrocoagulation process is an effective technique for treating various types of wastewater. In this work, the treatment of Ciprofloxacin (CIP) wastewater was optimized using Response Surface Methodology (RSM) with central composite design (CCD). RSM-CCD optimized the key factors such as solution pH, current intensity, and electrolysis time to attain maximum removal efficiency of (CIP). The second-order regression model and the empirical data were reasonably fit by ANOVA, which demonstrated a high coefficient of determination value (R2=0.9594). RSM-CCD estimation demonstrated that a pH of 4, a current intensity of 2 mA/cm2, and an electrolysis time of 60 min were the best operating parameters that achieved the maximum removal efficiency.